2016
DOI: 10.1111/ecca.12184
|View full text |Cite
|
Sign up to set email alerts
|

The Rising Postgraduate Wage Premium

Abstract: Despite post‐college degree holders now making up nearly 15% of the US adult workforce, studies of their labour market performance remain sparse. This is surprising given that they are the most educated group in the labour force and as, over time, they have done significantly better than all other education groups. We show a significant rise over time in the postgraduate wage premium, reflecting an increased relative demand due to their superior skill sets and occupational status. The increase in the demand fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 55 publications
1
45
0
1
Order By: Relevance
“…Therefore, we urge replication with more recent data to further scrutinize the association between undergraduate institutional mission and pursuit of advanced degrees; to determine whether incentives to pursue post-graduate training can boost enrollment and completion; and to better understand the welfare implications of the rising wage gaps among college graduates (Lindley & Machin, 2016; Valletta, 2015). Results showing higher advanced degree enrollment and completion rates among college graduates from institutions with limited research traditions coupled with relatively higher representation of black and Hispanic students at these institutions compared with research universities suggest a need to strengthen institutional bridges in ways that broaden the pipelines of underrepresented students to post-baccalaureate degrees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we urge replication with more recent data to further scrutinize the association between undergraduate institutional mission and pursuit of advanced degrees; to determine whether incentives to pursue post-graduate training can boost enrollment and completion; and to better understand the welfare implications of the rising wage gaps among college graduates (Lindley & Machin, 2016; Valletta, 2015). Results showing higher advanced degree enrollment and completion rates among college graduates from institutions with limited research traditions coupled with relatively higher representation of black and Hispanic students at these institutions compared with research universities suggest a need to strengthen institutional bridges in ways that broaden the pipelines of underrepresented students to post-baccalaureate degrees.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Valletta (2015) reports that wage gaps between BA and advanced degree recipients rose from 11 to 30 percent between 1970 and 2013, with the largest growth after 2000. Lindley and Manchin (2016) suggest that the relative growth in jobs requiring non-routine cognitive skills, such as management, medicine, law, and engineering, drove the higher wage gains of advanced degree holders, but they do not consider racial and ethnic variations among the college-educated. Whether and how the burgeoning minority population will contribute to wage differences among the college-educated depends on their transition to and completion of advanced degrees.…”
mentioning
confidence: 99%
“…Tamborini et al () found that college males and females have 43 per cent and 51 per cent wage premiums respectively over their lifetime compared to their high school counterparts. This study will focus on post‐graduate education because evidence of a positive relationship is stronger at the post‐graduate level (Lindley & Machin ). Race: an early study on racial earnings by Baldwin and Bishop () showed that the Black‐White wage gap increases as wages rise suggesting that access to education drives the gap. O’Neill et al () used standardised test scores to measure cognitive skill, and concluded that cognitive skill predominantly explains Whites’ higher earnings over Blacks and Hispanics.…”
Section: Independent Variables Data and Methodologymentioning
confidence: 99%
“…Część z nich ma charakter bardziej szczegółowy i pozwala na identyfikację premii z różnych typów wykształcenia wyższego, na przykład w podziale na studia I, II i III stopnia [np. Leigh, 2008;Hoeling i in., 2014;Lenton, 2016;Lindley, Machin, 2016]. Ich wyniki na ogół wskazują, że zarobki są tym wyższe, im wyższy stopnień studiów ukończono.…”
Section: Przegląd Literaturyunclassified